1.Przekształć iloczyny na sumy.
a) (√3 + 1)(2√3 - 2)
b) (√2 + √3)(√6 + √3)
c) (x√2 +1)(x - 2√2)
d) (x + √2)(2√2 + x)

2.Zapisz w postaci sumy algebraicznej:
a) (x + 1)(x + 2)(x + 3)
b) (x - 2)(x + 5)(2x - 1)
c) (x - 4)(x + 1)²
d) (2x - 3)²(x + 2)

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-08T19:45:27+01:00
1.
a)(√3+1)(2√3-2)=2√9-2√3+2√3-2
b)(√2+√3)(√6+√3)=√12+√6+√18+√9=2√3+√6+3√2+3
c)(x√2+1)(x-2√2)=x²√2-2x√4+x-2√2=x²√2-4x+x-2√2
d)(x+√2)(2√2+x)=2x√2+x²+4+x√2

2.
a)(x+1)(x+2)(x+3)=(x²+2x+x+2)(x+3)=x³+3x²+2x²+6x+x²+3x+2x+6
b)(x-2)(x+5)(2x-1)=(x²+5x-2x-10)(2x-1)=2x³-x²+10x²-5x-4x²+2x-20x+10
c)(x-4)(x+1)²=(x-4)(x²+2x+1)=x³+2x²+x-4x²-8x-4
d)(2x-3)²(x+2)=(4x²-12x+9)(x+2)=4x³+8x²-12x²-24x+9x+18


Oto chyba chodziło:)))